Efektivitas Pemberian Aplikasi Siper-B terhadap Pengetahuan, Kepercayaan Diri dan Keterampilan Ibu dalam Merawat Bayi Berat Lahir Rendah (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effectiveness of providing health education using audio-visual media, namely the application of SIPER-B (Information System for LBW Infant Care) on mothers' knowledge, confidence and skills in caring for low birth weight babies. The research method is quasi-experimental with a pre-test â€“ post-test control group design. The results showed that the knowledge, confidence and skills in the intervention group were higher than in the control group, with a grand mean of knowledge of 19.36, self-confidence of 5.48, skills of 7.88 and a p-value of 0.000. In conclusion, the SIPER-B application effectively increases mothers' knowledge, confidence and skills in caring for babies with low birth weight (LBW). Keywords: LBW, Confidence, Skills, Knowledge